2019
DOI: 10.1038/s41467-019-09582-3
|View full text |Cite
|
Sign up to set email alerts
|

The maternal to zygotic transition regulates genome-wide heterochromatin establishment in the zebrafish embryo

Abstract: The segregation of eukaryotic genomes into euchromatin and heterochromatin represents a fundamental and poorly understood process. Here, we demonstrate that genome-wide establishment of heterochromatin is triggered by the maternal to zygotic transition (MZT) during zebrafish embryogenesis. We find that prior to MZT, zebrafish lack hallmarks of heterochromatin including histone H3 lysine 9 trimethylation (H3K9me3) and condensed chromatin ultrastructure. Global establishment of heterochromatic features occurs fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
83
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 31 publications
(34 reference statements)
8
83
1
Order By: Relevance
“…We found a clear enrichment of H3K9me3 at methylated MOSAT_DR elements, whereas no other histone modification displayed any signal at these sites ( Fig.2d-e and Additional File1: Figure S5). H3K9me3 has been shown to mark the zebrafish genome pre-ZGA and to progressively increase from ZGA onwards [35,38], however, we find that at a sub-population of MOSAT_DR sites, H3K9me3 is stable during development (256 cell to shield) (Additional File1: Figure S5). This contrasts the observation in mammals, where H3K9me3 and mCH are generally inversely correlated at CG-poor regions [8,29,39].…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…We found a clear enrichment of H3K9me3 at methylated MOSAT_DR elements, whereas no other histone modification displayed any signal at these sites ( Fig.2d-e and Additional File1: Figure S5). H3K9me3 has been shown to mark the zebrafish genome pre-ZGA and to progressively increase from ZGA onwards [35,38], however, we find that at a sub-population of MOSAT_DR sites, H3K9me3 is stable during development (256 cell to shield) (Additional File1: Figure S5). This contrasts the observation in mammals, where H3K9me3 and mCH are generally inversely correlated at CG-poor regions [8,29,39].…”
mentioning
confidence: 71%
“…4hpf (GSM3484060, GSM3484068), 7hpf (GSM3484061, GSM3484069) and liver (GSM3505059) (https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE122722) [24]. ChIP seq datasets analysed in this study were taken from the following GEO records: H3K9me3 at 6hpf (GSM3096185, GSM3096186), 4.5hpf (GSM3096189, GSM3096190) and 2.5hpf (GSM3096193, GSM3096194) (https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE113086) [35]. H3K27me3 (GSM3165233) and H3K36me3 (GSM3165232) at dome stage (https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE114954) [37].…”
Section: Competing Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…We quantified this using an approach that was recently published (Laue et al, 2019) and found that the level of heterochromatin at 6dpf was significantly lower than at 1 and 3dpf (Figures S1D and E). This suggests that chromatin globally becomes more open at this timepoint.…”
Section: Electron Microscopy Reveals Different Nuage Types Between Dementioning
confidence: 99%
“…Heterochromatin formation is promoted by various pathways including those affecting covalent modifications of histones, which package DNA into nucleosomes, as well as cytosine methylation [5][6][7] . Chromatin states are re-established after fertilization of egg and sperm in diverse animals [8][9][10][11][12] , and histone reprogramming has also been observed in plants shortly after fertilization [13,14] . However, little is known about how heterochromatin-promoting pathways respond to labile chromatin states shortly after fertilization, and help re-establish euchromatic and heterochromatic states in animals and plants.…”
Section: Introductionmentioning
confidence: 99%